2017
DOI: 10.1155/2017/9402814
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Dendritic Cell Apoptosis and CD8+Cytotoxicity by Histamine: Role of Protein Kinase C

Abstract: Dendritic cells (DC) are able to present extracellular antigens associated with the molecules of the major histocompatibility complex class I. In a previous work, we demonstrated that the histamine (HIS), acting through H1/H4 receptors, increases the cross-presentation of soluble ovalbumin by murine DC and can enhance the recruitment of specific CD8+ T lymphocytes during the development of chronic inflammatory responses. Here, we studied in more depth the mechanisms underlying this enhancement. We showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In dendritic cells (DC) PKC-β expression and signaling is important in inducing DC differentiation (Cejas et al 2005). It was also reported that as DCs are involved in induction of chronic inflammatory diseases (Joffre et al 2012) PKCs regulate caspase-3-dependent apoptosis (Alcain et al 2017).…”
mentioning
confidence: 99%
“…In dendritic cells (DC) PKC-β expression and signaling is important in inducing DC differentiation (Cejas et al 2005). It was also reported that as DCs are involved in induction of chronic inflammatory diseases (Joffre et al 2012) PKCs regulate caspase-3-dependent apoptosis (Alcain et al 2017).…”
mentioning
confidence: 99%
“…We previously demonstrated that HA increases the recruitment of an unconventional profile of CD8 lymphocytes in the lungs of mice allergic to ovalbumin (31). Interestingly, when interacting with murine DCs, HA enhances the crosspresentation of antigens through the vacuolar pathway (32). Non-conventional CD8 lymphocytes of the Tc2 and/or Tc17 type have been described in allergic patients (8), a profile that is associated with the potentiation of the inflammatory response and the chronicity of these pathologies (3).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of cellular assays have been developed to determine the influence of peptide treatment on cell viability. As an early indicator of cell death, extracellular phosphatidylserine exposure, has been evaluated with Annexin V and propidium iodide (PI) fluorescent conjugates in OVA 257–264 peptide (SIINFEKL)-immunized dendritic cells treated with and without histamine, while carboxyfluorescein succinimidyl ester (CFSE) was used to monitor lymphocyte proliferation using flow cytometry . In this application, histamine enhanced the ability of dendritic cells to activate CD8 + T cells’ cytolytic activity in mononuclear spleen cells derived from immunized mice and cocultured with OVA-treated dendritic cells stained with CFSE.…”
Section: Selection Chemical Synthesis and Biological Evaluation Of De...mentioning
confidence: 99%
“…As an early indicator of cell death, extracellular phosphatidylserine exposure, has been evaluated with Annexin V and propidium iodide (PI) fluorescent conjugates in OVA 257−264 peptide (SIINFEKL)-immunized dendritic cells treated with and without histamine, while carboxyfluorescein succinimidyl ester (CFSE) was used to monitor lymphocyte proliferation using flow cytometry. 47 In this application, histamine enhanced the ability of dendritic cells to activate CD8 + T cells' cytolytic activity in mononuclear spleen cells derived from immunized mice and cocultured with OVA-treated dendritic cells stained with CFSE. Moreover, histamine reduced early stage apoptosis of dendritic cells induced by heat shock compared to the untreated controls, presumably due to the involvement of histamine activation of the protein kinase C pathway and its implications in regulating mitochondrial Ca 2+ flux associated with apoptosis.…”
Section: ■ Introductionmentioning
confidence: 97%